Hyperoodon ampullatus - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Hyperoodon ampullatus (Forster, 1770). In Kalm, Travels into N. Am., 1:18. TYPE LOCALITY: "See Mr. Pennant's [1769] British Zoology Vol. 3, p. 43, where it is called the beaked whale, and very well described;" Pennant (1769:43) gave Maldon (England) as the locality and 1717 as the date stranded. DISTRIBUTION: North Atlantic: arctic to cold-temperate waters. The Mediterranean record represents a stray (J. G. Mead, 1989b). STATUS: CITES - Appendix I; IUCN - Vulnerable. SYNONYMS: butskopf, latifrons, rostratus. COMMENTS: Reviewed by J. G. Mead (1989b). Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 361, DOI: 10.5281/zenodo.7352970